Ultrasound-guided Transversus Abdominis Plane Block as Rescue Analgesia following Failed Spinal Anaesthesia in a High Risk Patient: A Case Report - Karuna Taksande; Pardhasaradhi Kapusetti (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Opioid-free perioperative analgesia plays a crucial role in patients with significant co-morbidities and a prior history of opioidrelated respiratory depression. Achieving adequate analgesia using regional anaesthesia techniques is of importance in such cases. The present case report details the anaesthetic management of a 58-year-old male with a history of obesity, Obstructive Sleep Apnoea (OSA), stage 4 Chronic Kidney Disease (CKD), hypertension and opioid-induced respiratory depression who was scheduled to have a laparoscopic hernia repair. Spinal anaesthesia was chosen as the anaesthetic modality to avoid opioid usage. Inadequate neuraxial blockade necessitated General Anaesthesia (GA). The goal of an opioid-free anaesthetic technique was accomplished by using dexmedetomidine infusion and an ultrasound-guided bilateral Transversus Abdominis Plane Block (TAPB) for perioperative analgesia. The patient remained haemodynamically stable throughout the surgery without requiring vasopressors or opioids. Pain scores remained low in the recovery room with analgesia provided by paracetamol. There were no episodes of respiratory depression, sedation, nausea, or vomiting. The present case evidences the efficiency of ultrasoundguided TAPB plus dexmedetomidine as a safe opioid-sparing strategy after failed Neuraxial Anaesthesia (NA) in high risk patients undergoing laparoscopic abdominal surgery.